Antecedents to Faroese student teachers’ citizenship behaviour : A study of empirical relationships - Elstad, Eyvind; Harryson, Hans; Christophersen, Knut-Andreas Abben; Turmo, Are (Nordic Journal of Comparative and International Education (NJCIE), 2023)
The school is an important institution in Faroese society, as elsewhere in the world. Among other things, schools must prepare students for further education, professional life, and their duties as citizens. The quality of teachers’ instruction is the most important factor influencing pupils’ learning. The concept of citizenship behaviour highlights the idea that student teachers have a responsibility not only to fulfil their duties but also to contribute to the well-being of their peers. Student teachers’ citizenship behaviour is assumed to influence the functioning of teacher education. Teacher education prepares student teachers and supplies schools with appropriately trained teachers. The purposes of this study are (1) to present an overview of Faroese teacher training, and (2) to explore the statistical relationships between Faroese student teachers’ motivational orientations and their citizenship behaviours. As expected, we find that intrinsic motivation and extrinsic motivation are related to citizenship behavior. Furthermore, we find that instructional self-efficacy is positively related to citizenship behaviour. Implications for practice and avenues for further research are discussed.